2018
DOI: 10.1371/journal.pntd.0006866
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the economic impact of canine rabies to Viet Nam 2005–2014

Abstract: The global economic impact of canine rabies has been estimated by several studies. Asia bears a disproportionate burden of this zoonosis due to high levels of human deaths and rates of post-exposure prophylaxis (PEP), but low investment in preventative dog vaccination. The same factors that cause rabies to burden much of Asia are also present in Viet Nam. This study estimated the economic burden of canine rabies in a societal perspective including direct and indirect cost of rabies in dogs, livestock, and huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Study in Japan, the free rabies area, in contras said that implementation of annual vaccination of domestic dogs is very inefficient, it is probably because Japan has very low risk of rabies outbreak in past 26 years [14]. It will be very different with Indonesia which is rabies endemic area.…”
Section: Discussionmentioning
confidence: 99%
“…Study in Japan, the free rabies area, in contras said that implementation of annual vaccination of domestic dogs is very inefficient, it is probably because Japan has very low risk of rabies outbreak in past 26 years [14]. It will be very different with Indonesia which is rabies endemic area.…”
Section: Discussionmentioning
confidence: 99%
“…Rabies virus (RABV) is a non-segmented, negative-stranded RNA virus of the Rhabdoviridae, which causes rabies—a global public health threat and fatal viral zoonosis. RABVs spread to humans via biting or scratching of RABV-infected terrestrial mammals, such as bats (Ribeiro et al, 2018 ), dogs (Shwiff et al, 2018 ), and skunks (Leslie et al, 2006 ). As with various other infectious diseases, immunization methods for the human rabies vaccine are postexposure prophylaxis (PEP) rather than preexposure (Hampson et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of these bites are a result of human-derived antagonism and fear-based behaviors [11][12][13] . Several studies have reported rabies rates in biting dogs of less than 10% 5,9 . In many parts of the world diagnostic capacity and public health risk assessments are not available and rabies must be considered a possibility for every bite event.…”
mentioning
confidence: 99%